Usage of complementary and alternative medicine among primary care clinic attendees, Kuching, Sarawak, Malaysia - Siti Raudzah, Ghazali; Lee, Ping Yein; Abang Taha, Abang Bennett; Lin, Kyaw; Syed Hassan, Syed Ahmad Al-Mashoo (BMC Medical Genomics, 2007)
Aims: To evaluate the utilization of complementary and alternative medicine (CAM) in Kuching, Sarawak, Malaysia Methods: This was a cross-sectional study of patients who attended three randomly selected primary care clinics over 4 months from January to April 2004. A total of 198 patients were recruited. One hundred and eighty-one (91.4%) patients agreed to participate by answering the anonymous questionnaire. Results: Ninety (51.4%) patients used CAM of which 43 (47.8%) patients used more than one type of CAM. Utilization rates of CAM were found to be associated with employment status but not with other socio-demographic factors. The common types of alternative medicine used were massage (n = 63; 36.2%) and herbal medicine (n = 44; 25.1%). Forty-two (46%) of the CAM users, used CAM for the problems that led to their current clinic visit. Thirty-four (37.8%) were using alternative and modern medicine at the same time. The reasons for CAM usage given by about half of the patients were that CAM was more effective and better for emotional or mental health problems. Conclusions: Usage of CAM was common in patients who visited primary care clinics. It is important to recognize this fact as combined use of CAM can create potentially dangerous interactions with pharmacotherapies.